Atividade das enzimas celulase e xilanase durante a decomposição anaeróbia de macrófitas aquáticas - Nunes, Maíra de Figueiredo (2010)
Enzymatic activity during decomposition is extremely important to hydrolyze molecules that are assimilated by microorganisms. During aquatic macrophytes decomposition, enzymes act mainly in the breakdown of lignocellulolytic matrix fibers (i.e. cellulose, hemicellulose and lignin) that encompass the refractory fraction from organic matter. Considering the importance of enzymatic activities role in decomposition processes, this study aimed to describe the temporal changes of xylanase and cellulase activities during anaerobic decomposition of the aquatic macrophytes community located at Óleo Lagoon, placed in Ecological Station of Jataí, Luiz Antonio, São Paulo, Brazil. After a survey of existing aquatic macrophytes, 10 species were indentified in the lagoon. They were collected and bioassays were accomplished in the laboratory. Decomposition chambers from each species (n = 10) were set up with dried macrophyte fragments and filtered Óleo Lagoon water. The chambers were incubated at 22.5oC, in the dark and under anaerobic conditions. Enzymatic activities and remaining organic matter were measured periodically during 90 days. Besides this analysis, pH, humification index and carbon types were evaluated. Initial cellulose and hemicellulose was measured for each species. For all the plants xylanase s activitiy was greater than cellulase activity. The results showed no correlation between organic matter decay and enzyme production. This could have occurred because of lignocellulolytic matrix fibers structural differences and also because of physical, chemical and biological characteristics. The incubations showed a low pH, what agrees with Óleo lagoon characteristics, supporting that aquatic macrophytes decomposition interfers in its physical and chemical characteristics. Egeria najas presented a dissolved organic carbon (DOC) accumulation pattern during its decomposition which differed from the other species. This pattern tends to accumulate humic substances and consequently alters some water characteristics. Besides it, E. najas presented the largest distribution over Óleo lagoon area. Emergent species presented the greater amount of particulate organic matter (POM) accumulated in sediment, configuring the main available substrate to anaerobic microorganisms.